2017
DOI: 10.1111/cas.13336
|View full text |Cite
|
Sign up to set email alerts
|

Tumor endothelial cells accelerate tumor metastasis

Abstract: Tumor metastasis is the main cause of cancer‐related death. Understanding the molecular mechanisms underlying tumor metastasis is crucial to control this fatal disease. Several molecular pathways orchestrate the complex biological cell events during a metastatic cascade. It is now well known that bidirectional interaction between tumor cells and their microenvironment, including tumor stroma, is important for tumor progression and metastasis. Tumor stromal cells, which acquire their specific characteristics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(196 citation statements)
references
References 58 publications
(116 reference statements)
4
191
0
1
Order By: Relevance
“…During angiogenesis, tumor growth changes from slow to rapid; angiogenesis is the key step to facilitate this transformation. Inhibition of angiogenesis can obviously control tumor growth and metastasis . In this study, we found that miR‐873 suppression conspicuously enhanced the viability and growth of PC9 cells treated with gefitinib.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…During angiogenesis, tumor growth changes from slow to rapid; angiogenesis is the key step to facilitate this transformation. Inhibition of angiogenesis can obviously control tumor growth and metastasis . In this study, we found that miR‐873 suppression conspicuously enhanced the viability and growth of PC9 cells treated with gefitinib.…”
Section: Discussionmentioning
confidence: 57%
“…Inhibition of angiogenesis can obviously control tumor growth and metastasis. [45][46][47][48][49] In this study, we found that miR-873 suppression conspicuously enhanced the viability and growth of PC9 cells treated with gefitinib. Moreover, the inhibition of miR-873 increased angiogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…While the ECs help in the formation of new blood vessels to assist tumour growth and metastasis [40], fibroblasts, CAFs secrete growth factors [41,42] and contribute to ECM remodelling. The presence of ECs as revealed by positivity to CD31 marker was identified in all the 12 RB tumours assessed, and these cells were majorly found localised in the blood vessels of RB tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer metastasis involves a complex cascade of events: tumor cells i) invade the surrounding stroma and extracellular matrix; ii) intravasate into the bloodstream and survive in the blood circulation; iii) arrest at distant organ sites; and iv) extravasate and invade into the parenchyma of distant tissues [21,22]. Some enriched functional lists were found to be associated with these cascades during this process and to be present only in tumor-forming rats.…”
Section: Functional Analysismentioning
confidence: 99%